Role of tomosynthesis in breast imaging going forward. Issue 4 (April 2018) - Michell, M.J.; Batohi, B.
Abstract : Digital breast tomosynthesis (DBT) is a modified mammographic technique that overcomes some of the limitations of full-field digital mammography (2DDM) by eliminating the effect of overlapping breast tissue. In the UK, DBT is utilised in both the symptomatic setting and in breast screening assessment clinics. A literature search was conducted from 2010–2017 to ensure that the most recent developments in DBT technology, clinical applications, and assessment of its usefulness in breast screening were reviewed. Technological advances in DBT include the addition of synthetic 2D mammograms, which are generated from the DBT data set, and the use of DBT to guide vacuum-assisted biopsy and excisions. The units from each vendor vary in several aspects, which are detailed in this article. DBT improves diagnostic accuracy and reader confidence when identifying benign and malignant lesions. It has also been shown to be more accurate than 2DDM in assessing tumour size and in the assessment of multifocal tumours. In the screening setting, retrospective reader studies have shown that the addition of DBT to 2DDM showed equivalent or an improvement in sensitivity and specificity when compared to 2DDM alone. Many of these trials showed an increase in invasive cancer detection and a reduction in recall rates. Large prospective randomised controlled trials conducted in Europe and North America will evaluate effectiveness, practicalities, and cost implications of utilising DBT in routine breast screening practice.